SAT0096 Mean Platelet Volume as a Biomarker Representing Seropositivity and Treatment Responses in Rheumatoid Arthritis - Lee, Y.-A.; Hong, S.-J.; Lee, S.-H.; Yang, H.-I.; Kim, K. Y. (Annals of the rheumatic diseases, 2013)
Background Chronic inflammation is known to be associated with increased cardiovascular (CV) event rate in rheumatoid arthritis (RA). Platelet activation may be a link in the pathophysiology of diseases leading to thrombosis and inflammation. Mean platelet volume (MPV), a platelet index, is an indicator of platelet activation. Several studies have shown increased MPV in RA patients compared to controls. But, the others reported that a RA patient may present a decreased MPV during active stages and later on will increase by different treatment regimens. Thus far, it is still not clear whether MPV increases or decreases with RA disease activities and over the duration of treatment. Objectives The current study was conducted to evaluate platelet function by measuring MPV in a selected population of newly diagnosed and untreated RA subjects. We also aimed to assess associations between MPV and seropositivity or other inflammatory markers. Finally we investigate the changes of MPV in response to disease-modifying anti-rheumatic drugs (DMARDs). Methods Newly diagnosed and DMARDs naïve RA patients were recruited. We excluded those with established CV diseases or any conventional CV risk factors such as diabetes, hypertension, hyperlipidemia and smoking. Finally 92 RA patients (74 females, age: 49.8 ± 13.8 years) and 160 age- & sex- matched healthy subjects (120 females, age: 49.1 ± 11.6 years) as controls were enrolled for analysis. All patients started to receive DMARDs therapy including biologic agents (MTX: 70;76.1%, anti-TNF-alpha: 12;13.0%). They underwent thorough clinical and laboratory evaluation including MPV, platelet count, rheumatoid factor, anti-CCP, ESR, and CRP at baseline, 3 months, 6 months and 12 months. Seroposivity was defined to be positive for RF or anti-CCP. Results At baseline, MPV was lower in RA patients as compared to healthy controls (7.985 ± 0.916 vs. 7.988 ± 0.538 fL, p=0.002) and was negatively correlated with platelet counts and ESR levels (r:-0.244; p=0.022, r:-0.205; p=0.058, respectively). But, MPV was not correlated with the other inflammatory markers in patients with RA. Additionally, among RA patients, seropositive RA patients showed the significantly lower level of MPV than seronegative RA (7.973 ± 0.592 vs. 8.024 ± 1.580 fL, p=0.013). DMARDs therapy resulted in a significant increase in MPV only at 12 months after initiating treatment (7.985 ± 0.916, 8.015 ± 0.882, 7.926 ± 0.785, and 8.390 ± 0.766 fL at baseline, 3 months, 6 months and 12 months*, respectively; *p<0.000). Conclusions The result of this study provides additional evidence supporting the previous reports that MPV is lower in active RA. We also found the correlation of MPV with seroposivity and long-term treatment response to DMARDs in RA patients. A decrease of platelet size as a result of increased turnover seems to be a mirror activity of RA. Disclosure of Interest None Declared